Synthesis and Characterization of Polybenzoxazinone and its Prepolymer Using Gas Separation. Issue 24 (28th October 2013) - Pientka, Zbyněk; Brozova, Libuše; Pulyalina, Alexandra Y.; Goikhman, Mikhail Y.; Podeshvo, Irina V.; Gofman, Iosif V.; Saprykina, Natalia N.; Polotskaya, Galina A.
<x xml:space="preserve">Abstract</x> Polybenz‐3, 1‐oxazinone‐4 (PBOZ) films are prepared via the thermal rearrangement of poly[(methylene‐bis‐anthranilamide) 4, 4′‐diphenyloxidicarboxylic acid] (PAA) films by heating to 300 °C. PAA is synthesized by low‐temperature polycondensation. The PBOZ film exhibits excellent mechanical properties and a high glass‐transition temperature. Conversion of PAA to PBOZ leads to an increase in the fractional free volume as a result of thermal dehydration and cyclization during membrane formation and due to the removal of residual solvent. The excess free volume in the PBOZ film is approximately 3–4% of the total volume. The gas permeability and selectivity of the PBOZ film is higher than that of the PAA film. The thermal rearrangement of polymers is recognized as a suitable method to improve separation efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>